Teacher Education within the Peripherals of Positive Education - Girdhar, Meenakshi (JOURNAL OF INDIAN EDUCATION, 2018)
Positive education has a mandate for academic skill development, complemented with approaches that nurture well-being and promote good mental health. It is an added boon in the field of education which aims to churn out a healthy society, procuring the well-being of all its citizens. In the present paper, the author has set out to uncover the threefold aspect, discussed as follows. To explore the concept of positive education To strengthen the justification and need of imbibing positive Teache Education in teacher education programme, and To explore out sub-dimensions of positive Teacher Education (influenced fro Geelong Grammar School’s Model of Positive Education) with a purpose to get a pilot project done in the field of Teacher Education in India.